A Review Study of the Temperature and Salinity of Southern Iranian Waters in 2005 - 2012 Using WOA13 Data - Danial Ghaderi; Mostafa Solgi; Mehrnaz Farzin Gohar (Nīvār)
In this study, considering the importance of temperature and salinity parameters in recognizing marine phenomena, changes of these parameters were investigated using WOA13 data and the conditions of each of these parameters were determined at different seasons and at different depths. Therefore, by selecting WOA13 historical data, which is the seasonal mean of temperature and salinity over the period 2005 to 2012, IDW interpolation maps of salinity and temperature at the surface, 5, 20 and 50 m were performed. In order to understand how these parameters change in depth, vertical profile cross sections maps have been created in 6 different lines. Also, the results are compared with the studies in the study area. According to the data and results it can be concluded; As the seasons change from winter to summer, salinity and temperature increase from the Oman Sea to the northern part of the Persian Gulf and decrease with autumn, This well describes the thermohaline cycle of the region. It also experiences the highest and lowest salinity in the northern part of the Persian Gulf and the Oman Sea, respectively. And, the highest and lowest temperatures, respectively, are in the central part of the Persian Gulf (summer season) and the northern part of the Persian Gulf (in winter and spring).